HIV/HCV Co-infection, Liver Disease Progression, and Age-Related IGF-1 Decline - Jeffrey Quinn; Jacquie Astemborski; Shruti H. Mehta; Gregory D. Kirk; David L. Thomas; Ashwin Balagopal (Case Western Reserve University, 2017)
Background: We have previously reported that persons co-infected with HIV and hepatitis C virus (HCV) had liver disease stages similar to HIV-uninfected individuals who were approximately 10 years older. Insulin-like growth factor 1(IGF-1) levels have long been known to decline with advancing age in humans and non-humans alike. We examined whether HIV infection affects the expected decline in IGF-1 in persons with chronic hepatitis C virus (HCV) infection and if that alteration in IGF-1 decline contributes to the link between HIV, aging, and liver disease progression. Methods: A total of 553 individuals with HCV infection were studied from the AIDS Linked to the Intravenous Experience (ALIVE) cohort for whom more than 10 years of follow-up was available. Serum IGF-1 levels were determined by ELISA and evaluated according to baseline characteristics and over time by HIV status and liver disease progression. Linear regression with generalized estimating equations was used to determine whether IGF-1 decline over time was independently associated with liver disease progression. Results: Baseline IGF-1 levels were strongly associated with age (P < 0.0001) but not with gender or HIV infection. Levels of IGF-1 declined at a rate of -1.75 ng/mL each year in HCV mono-infected individuals and at a rate of -1.23 ng/mL each year in HIV/HCV co-infected individuals (P < 0.05). In a multivariable linear regression model, progression of liver fibrosis was associated with HIV infection and age, as well as with a slower rate of IGF-1 decline (P = 0.001); however, the rate of IGF-1 decline did not alter the strength of the associations between HIV, liver disease, and age. Conclusions: The normal decline in IGF-1 levels with age was attenuated in HIV/HCV co-infected individuals compared to those with HCV mono-infection, and slower IGF-1 decline was independently associated with liver disease progression. Keywords: IGF-1, HIV-1, Hepatitis C, Fibrosis, Liver